The Effects of Work Efficiency, Progress Monitoring, and Digital Collaboration on Human Resource Performance in a Digital-Based Certification Institution - Hadi Prastyo; Ike Kusdyah Rachmawati; Yunus Handoko (Journal of Educational Management Research, 2026)
This study examines the effects of work efficiency, progress monitoring, and digital collaboration on employee performance within the context of digital transformation in a certification institution. The research aims to analyze both the partial and simultaneous influence of these three factors on employee performance during the transition to a digital-based work system. A quantitative approach was employed using a survey method involving 40 respondents selected through purposive sampling. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression, t-tests, F-tests, and the coefficient of determination. The findings reveal that, partially, work efficiency has a positive and significant effect on employee performance, while progress monitoring and digital collaboration do not show a significant individual effect. However, simultaneously, all three variables significantly influence employee performance, indicating a strong explanatory power of the regression model. These results suggest that the success of digital transformation in certification institutions is primarily supported by improved work efficiency and the integrated implementation of digital management practices. The study implies that education and training institutions undergoing digital transformation should prioritize efficiency-oriented digital strategies while strengthening the synergy between monitoring systems and digital collaboration to enhance overall employee performance.